Memórias do parir: reflexões sobre a forma como nascemos - Souza, Dejaina Dias de (2023)
This research is located in the area of Anthropology of Childbirth and seeks to understand, from the memories of the period of pregnancy and childbirth of six women, their perceptions regarding pain, the body and the ability to give birth, in addition to understanding the types of practices practiced in the technocratic obstetric model, prevalent in Brazil, where the supremacy of the medical discourse seems to overlap with the cultural aspects of women, often making it impossible for them to be integral protagonists in the parturition process. Through semi-structured interviews, six women aged between 31 and 80 years were heard, between the months of January and March 2022, who underwent different types of delivery: natural, normal and cesarean section, at home and in health institutions, in the State of Sergipe.